리눅스에 적용된 해시 및 암호화 알고리즘 분석 - 배유미; 정성재; 소우영; Bae, Yu-Mi; Jung, Sung-Jae; Soh, Wooyoung (한국항행학회논문지, 2016)
MD-5 has been the hash algorithm to encrypt the user's password on Linux from the beginning. Recently the more reliable password management was demanded and SHA-512 algorithm became the hash algorithm on the recent Enterprise Linux which is more reliable than MD-5. This paper researching the characteristics of the hashing and encryption algorithms and find out about Linux User information management. Based on this analysis, and analysis of the security of the hashing algorithm is applied to the user password. In addition, analyzes the cases used hash algorithm applied to the validation of Open Source Software file, such as Apache, PHP, MySQL. Finally, by analyzing the security tool John The Ripper this paper suggests the enhanced security with the administrative management of passwords. 리눅스는 초창기부터 사용자 패스워드의 암호화를 위해 해시 알고리즘인 MD-5를 사용해 왔다. 최근 보안성이 강화된 패스워드 관리가 요구되면서 엔터프라이즈 리눅스 시스템에서는 MD-5보다 더욱 높은 신뢰성을 보이는 SHA-512 알고리즘을 사용하고 있다. 본 논문에서는 해시 및 암호화 알고리즘의 특징에 대해 비교 분석하고, 리눅스 사용자 정보의 관리 체제에 대해 알아본다. 이러한 분석을 기반으로 사용자 패스워드에 적용된 해시 알고리즘의 보안성에 대해 분석하고, 추가적으로 Apache, PHP, MySQL과 같은 공개 소프트웨어 파일 검증에 사용되는 해시 알고리즘 적용 사례를 분석한다. 마지막으로 관련 보안 도구인 John The Ripper를 분석하여 사용자 패스워드 관리를 통한 시스템 보안 강화 방법을 제시한다.